O direito fundamental ao trabalho decente como condição de emancipação da trabalhadora doméstica no ordenamento jurídico brasileiro - Mello, Ana Karolina Costa (2021)
This dissertation aims to verify whether the treatment of labor relations concerning the domestic sphere in the Brazilian legal system is in line with the concept of decent work in order to effect recognition and emancipation for domestic workers. Decent work was defined as one that confers working conditions that allow the preservation of the worker's dignity and that respect human rights, so that work allows the development of the emancipated subject, so that they can develop their freedoms in social institutions. The premises of the Theory of Fundamental Rights were analyzed, on which the conception of decent work is based. This conception filtered the legal and socio-political analysis of domestic work in Brazil, with the objective of verifying the violation of the principle of equality in these relations. Axel Honneth's Theory of Recognition was analyzed in conjunction with a social analysis of the situation of domestic workers in Brazil, concluding that the legal treatment given to the domestic class was based on the violation of the principle of equality, on the basis of gender and race discrimination; consequently, not being aligned with the concept of decent work that guides international and national labor relations. Through conflict and social struggles as a way to promote the ethical change in institutional relations, these social actors have managed to advance in the consolidation of their rights, a struggle that has not yet come to an end. Finally, as a practical measure to promote decent work, a professional qualification was proposed as a way of directing domestic work relations in Brazil to the approximation of the principles of equality and freedom. The research was based on the deductive perspective through bibliographic analyzes.